LEVEL OF KNOWLEDGE AND ITS APPLICATION BY COFFEE FARMERS IN THE UDEEN AREA, GOVERNORATE OF IBB - REPUBLIC OF YEMEN - Abdullah A. Al-Zaidi; Mirza B. Baig; Mohammad Y. Shalaby; Abdulwahaab Hazber (Journal of Animal and Plant Sciences, 2016)
This study estimated the knowledge and its application by coffee farmers in Udeen, lbb Governorate, Yemen. A total of 200 farmers, representing 86% of the coffee farmers, were interviewed using a questionnaire. Percentages, arithmetic means, standard deviations, and Pearson correlation coefficients were calculated. Approximately 51% of respondents had low and 6.5% had high levels of knowledge, and 49% of the respondents showed low and 12.5% respondents exhibited high knowledge application rates. Positive correlations were found between the degrees of knowledge and its application, educational qualifications, land tenure, area under coffee cultivation, extension service satisfaction, and exposure to sources of information (P ≤ 0.01). However, there was a negative relationship for the age of the respondent and type of tenure (P ≤ 0.01). There was no significant relationship for the number of family members, occupation, other agricultural activities, annual income from the coffee crop, and full-time agricultural work. The results suggest a need to increase extension activities to bridge the knowledge gap and improve application rates. Agricultural programs need to be developed for the coffee growers. Finally, agricultural extension programs through television and radio could raise the awareness of the importance of coffee in Yemen.
Keywords: Coffee production; Constraints; Extension education; Radio and TV programs; Entrepreneurship